2017
DOI: 10.1136/bmjopen-2016-015008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the diagnostic accuracy of PCR-based detection ofStreptococcus pneumoniaefrom nasopharyngeal swabs collected for viral studies in Canadian adults hospitalised with community-acquired pneumonia: a Serious Outcomes Surveillance (SOS) Network of the Canadian Immunization Research (CIRN) study

Abstract: Study designDetection and serotyping of Streptococcus pneumoniae are important to assess the impact of pneumococcal vaccines. This study describes the diagnostic accuracy of PCR-based detection of S. pneumoniae directly from nasopharyngeal (NP) swabs collected for respiratory virus studies.MethodsActive surveillance for community-acquired pneumonia (CAP) in hospitalised adults was performed from December 2010 to 2013. Detection of pneumococcal CAP (CAPSpn) was performed by urine antigen detection (UAD), identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(45 reference statements)
0
4
1
Order By: Relevance
“…This study revealed a 100% sensitivity of M-PCR in detection of H. influenzae and S. pneumoniae compared to culture method. In contrast to the current research, Gillis et al [ 26 ] showed that PCR based method had poor sensitivity in detection of S. pneumoniae in nasopharyngeal swabs of CAP patients. This discrepancy may be due to the differences in sample types, as we used sputum samples in the current study.…”
Section: Discussioncontrasting
confidence: 80%
“…This study revealed a 100% sensitivity of M-PCR in detection of H. influenzae and S. pneumoniae compared to culture method. In contrast to the current research, Gillis et al [ 26 ] showed that PCR based method had poor sensitivity in detection of S. pneumoniae in nasopharyngeal swabs of CAP patients. This discrepancy may be due to the differences in sample types, as we used sputum samples in the current study.…”
Section: Discussioncontrasting
confidence: 80%
“…However, the magnitude of the PPA increase in our study was lower, supporting the use of a cutoff at ≥10 4 copies/mL in NP for S. pneumoniae diagnostic to keep a high NPA. ( 15 17 ). To our knowledge, our study is the first that evaluates different RT-PCR cutoffs in NP for H. influenzae .…”
Section: Discussionmentioning
confidence: 99%
“…Although molecular tests in NP swabs are accepted for viruses and atypical bacteria such as Mycoplasma pneumoniae and Chlamydia pneumoniae ( 14 ), few studies evaluated their performance on upper respiratory tract samples (URT) for the most common bacterial causes of community-acquired LRTIs, such as Streptococcus pneumoniae , Haemophilus influenzae , and Moraxella catarrhalis . Four studies evaluated identification of S. pneumoniae by real-time PCR (RT-PCR) in NP specimen of patients with community-acquired pneumonia (CAP) with negative percent agreements (NPA) of >90% but with wide differences in positive percent agreement (PPA; 35% to 82%) using standard microbiological tests as gold standard ( 15 18 ). No study evaluated the validity of PCR in the NP swabs for other bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The development of molecular methods and increasing knowledge of S. pneumoniae virulence determinants together with a better understanding of genetic diversity of pneumococci and other Mitis streptococci led to proposing several targets for PCR and real-time PCR in order to improve species identification among Mitis streptococci, especially concerning their questionable representatives. As PCR-based approaches do not require cultured microorganisms, they find also an application in the direct detection of pneumococci in clinical materials [55,56], including polymicrobial samples [57][58][59][60].…”
Section: Pcr-based Methods Of Identificationmentioning
confidence: 99%